INVESTIGASI FAKTOR PENYEBAB COST OVERRUN OLEH KONTRAKTOR PADA PROYEK JALAN APBD KABUPATEN KARANGANYAR TAHUN 2017 DAN 2018 - Muhammad Nur Sahid; Niza Widiana (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2021)
The rapid development of road project development cannot be separated from the cost problem which often experiences cost overrun. This swelling can occur if a project management and control is not going well and does not meet the project target. The study was conducted to see the dominant factors that caused the cost overrun by the contractor for the implementation of the Karanganyar District Budget in Central Java Province which took place in 2017 and 2018, by distributing questionnaires to contractors. The results of the respondents collected were 36 respondents with 27 respondents. The questionnaire was processed by data processing using the SPSS (Statistical Package for Social Sciences) version 25 program. Reliability testing of 36 questionnaires showed that there were three unreliable questionnaires. In addition, the validity results of several variables in the questionnaire were obtained, namely one invalid variable. In addition to the validity and reliability tests, parametric statistical tests and multiple linear analysis were also carried out, then the results of the dominant factors that led to the implementation of Cost Overrun were schedule due to the influence of weather, disasters, poor cost control, not taking into account unexpected costs, and interest rates. bank loans, as well as the proportion of dominant cost overruns that occurs between 1% -5%